Selecting correct architecture for mission critical safe control systems - Dogruguven, E. H.; Ustoglu, I. (CRC PRESS-BALKEMA, 2018)
Developing safety critical systems require long years of planned investments, broad theoretical knowledge and domain experience. Data interchange between CPUs, synchronization, computation speed and diagnostic measures shall exhaustively be evaluated along with the effects of the parameters used in the reliability and safety calculations ex tunc. This study focuses on the effects of calculation parameters for different architectures. Special attention is paid for the architecture 1oo2D regarding its model and normative definition. It has also been revealed that there are correlations between some parameters which seem independent. An advising route map is created to distill what kind of methods can be applied to decrease the hazard rates. For concretizing some concepts and sharing field experience, railway domain is selected, however the study is fully applicable to other domains due to deeming the norm IEC 61508 along the entire paper.
Keywords: FAILURES; Engineering